Guidelines on Measurement of Well-being - United Nations Economic Commission for Europe (United Nations, 2025)
The Guidelines are targeted at national statistical offices. The guidelines focus on the measurement of well-being ‘here and now’, a subset of a broader conception of well-being that also considers well-being ‘elsewhere’ and ‘later’. The Guidelines provide recommendations on the dimensions of well-being, on the selection and compilation of statistical indicators, data sources and the dissemination and communication of well-being indicators to the public.